Evaluation of Public Street Lighting (PJU) on Jalan Ratu Sepudak, Singkawang City - Saputra, Andi; Junaidi, Junaidi; Gianto, Rudy (Faculty of Engineering, Universitas Tanjungpura, 2025)
Public Street Lighting (PJU) is a lighting installation that is public and usually installed on roads, bridges and certain places such as parks and other public places. Public Street Lighting (LPJU) is a lamp used for street lighting at night so that it makes it easier for pedestrians, Cyclists and motorists can see more clearly the road / terrain that will be passed at night, so as to improve traffic safety, comfort of road users and provide security from criminal activities. On Jalan Ratu Sepudak Kota Singkawang, 41 light points have been installed using single ornament, the lamps used are 150 Watt SON-T type, The distance between the poles is 30 - 50 meters. Based on the results of the evaluation carried out, the results of 100 Watt LED lamps with a pole height of 9 meters, the handlebar ornament angle is 19.940, the number of light points is 58 points, illumination is 6.23 lux, the power needed is 5.8 kWh / day, and the energy consumption needed is 69.6 kWh / day.